Exosomes derived from microRNA‐21 overexpressed adipose tissue‐derived mesenchymal stem cells alleviate spine osteoporosis in ankylosing spondylitis mice. (19th April 2022) - Hu, Lisheng; Guan, Zhiping; Tang, Chenfeng; Li, Guoxin; Wen, Jian
Abstract: MicroRNA‐21 (miR‐21) can induce proliferation and differentiation of mesenchymal stem cells (MSCs) to promote bone formation, we therefore aimed to investigate whether exosomes derived from miR‐21 overexpressing adipose tissue‐derived MSCs (AD‐MSCs) could improve spine osteoporosis in ankylosing spondylitis (AS) mice. Cultured AD‐MSCs were transfected with lentivirus vectors containing miR‐21 or control vector, and the supernatant was centrifugated and filtrated to harvest the exosomes (miR‐21‐Exos or vector‐Exos). BALB/c mice were immunized with cartilage proteoglycan to establish proteoglycan‐induced ankylosing spondylitis (PGIA) model. Six weeks later, PGIA mice were further injected with miR‐21‐Exos or vector‐Exos. Transfection of miR‐21 in AD‐MSCs significantly enhanced miR‐21 levels in AD‐MSCs and their exosomes. miR‐21‐Exos showed concentration‐dependent protective effect against spine osteoporosis in PGIA mice, evidenced by increased bone mineral content and bone mineral density, reduced number of osteoclasts, decreased content of deoxypyridinoline in the urine, decreased content of tartrate‐resistant acid phosphatase (TRACP)‐5b and cathepsin K in the serum, and down‐regulated interleukin (IL)‐6 expression in the spine, whereas vector‐Exos did not show any treatment benefit. The above findings indicate that miR‐21‐Exos could be utilized to treat spine osteoporosis in AS.